2001
DOI: 10.1093/ije/30.5.983
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and incident coronary heart disease in Chinese, Malay and Asian Indian males: the Singapore Cardiovascular Cohort Study

Abstract: The increased susceptibility of Asian Indian males to CHD has been confirmed in a longitudinal study. All of the examined established risk factors for CHD were found to play important but varying roles in the ethnic groups in Singapore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
84
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(91 citation statements)
references
References 27 publications
5
84
2
Order By: Relevance
“…The patient has been hospitalized to the Ipoh GH may had control their diet program. These findings were similar with one study from Singapore with almost same ethnic background (Lee et al, 2001). …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The patient has been hospitalized to the Ipoh GH may had control their diet program. These findings were similar with one study from Singapore with almost same ethnic background (Lee et al, 2001). …”
Section: Discussionsupporting
confidence: 92%
“…It can be divided into two, which are controllable and uncontrollable risk factors. (Milinow, 1990;Bostom et al, 1999;Kuulasmaa et al, 2000;Lee et al, 2001;D'Agostino et al, 2000;ESCHDCRG, 1998;Karim et al, 2000;O'Malley et al, 2000). Despite a lot of investigation for novel risk factor, established risk factors still play a major role for CVD (Kuulasmaa et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enas et al in their study on coronary artery disease in Indians (CADI) study reports the prevalence of diabetes to be three to six times higher among south Asian's than Europeans, Americans and other Asians [9] which is also observed in this patient, showing fasting glucose as 186 mg/dL predicting high blood glucose levels with hypertriglyceridemia. We Indians have relatively higher risk of predisposition to coronary artery disease even at relatively lower level of cholesterol [10] . Further hospital based study also observed lower levels (<200 mg/dL) of cholesterol in 75% of patients with myocardial infarction which is indicative of the fact that we have lower threshold for the total cholesterol levels compared to western population adding to further risk of CAD [11] .…”
Section: Discussionmentioning
confidence: 98%
“…3,16,17 Furthermore, weight gain was associated with an increased incidence of cardiovascular disease among middle-aged men. [16][17][18] However, few prospective studies in Asian countries have examined associations of BMI 19,20 and weight change with the incidence of coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%